Effects of ingredient and processing conditions on the rheological properties of whole wheat flour dough during breadmaking - A review. (February 2023) - Sun, Xinyang; Wu, Simiao; Koksel, Filiz; Xie, Minhao; Fang, Yong
Abstract: To benefit the consumers with a variety of health benefits, the incorporation of wheat bran into the bread formula has been widely conducted. This leads to changes in the rheological properties of dough that is associated with the overall quality of bakery products. This review has demonstrated the utility of a wide range of measurements at large and small deformations for determining dough rheological properties. Particularly, the rheological models have been proven with a good application in characterizing the viscoelastic behavior of whole wheat dough during breadmaking. The objective of this review was to build up a solid theorical foundation on how the rheological properties and baking performance of doughs are modified by manipulating the ingredient ( i.e., the composition of gluten proteins from refined wheat flour, the properties of dietary fibre, the flour particle size, and the addition of hydrocolloids and enzymes) and processing ( i.e., the time, temperature, speed and work input of mixing, the time, speed and geometry type of kneading, and the resting time) conditions throughout breadmaking processes. We also aimed to demonstrate the interactions of gluten proteins, dietary fibre and water molecules that play critical roles in affecting the dough rheology and the resultant bread quality. This will bring us a future research focus on how the gluten protein-dietary fibre-water interactions respond to the effects of dough formulation and processing parameters. Graphical abstract: Image 1 Highlights: Whole wheat dough rheology was determined at large and small deformations. Rheological models have a good application in describing dough rheology. Ingredients and processing affect dough rheology and baking performance. Gluten protein-dietary fibre-water interactions were affected by dough formulation.